Jack Frost : the end becomes the beginning - Joyce, William, 1957- (Joyce, William, 1957- Guardians, 2018)
After Nightlight, a Guardian, transforms into Jack Overland Frost, he is entrusted by Father Time with a great secret, but he must revisit his past if he is to understand the secret and defeat an old enemy who threatens the world with destruction.